The Influence Between Place of Residence and Disaster Adaptation Capacity Among Generation Z - Putri, Dhiya Ulhaq Riyan; Rafi, Muhammad; Widodo, Sugeng; Abdurrahman, Abdurrahman; Utami, Rahma Kurnia Sri; Suhendro; Saleh, Yazid (Jurnal Penelitian Geografi, 2025)
Lampung Province is categorized as a highly vulnerable area due to its proximity to the Indian Ocean, the Sunda Strait, and the volcanic activity of Anak Krakatau. This geographical setting poses significant adaptation challenges, particularly for Generation Z, a strategic age group in disaster mitigation. This study aims to examine the relationship between place of residence and tsunami disaster adaptation capacity among Generation Z, with a specific focus on geographical proximity to the Megathrust and Krakatau Volcano. A quantitative approach was employed through an online survey distributed to 261 students of the University of Lampung. Data were analyzed using descriptive non-inferential statistics and multiple linear regression. The results indicate variations in disaster literacy levels across regions, with the highest scores reported by respondents from Bekasi (100) and Prabumulih (98), while the lowest scores were observed in Musi Banyuasin (66.5) and Medan (69.67). However, regression analysis revealed that geographical distance from either the Megathrust or Krakatau had no significant effect on tsunami literacy (Sig. > 0.05). These findings highlight that distance is not the primary determinant; rather, disaster experience, access to information, education, and local policy play a more substantial role in shaping the preparedness of Generation Z. The study recommends integrating disaster literacy into higher education curricula and strengthening evacuation simulations as adaptive strategies